Durability of output and expected stock returns - Gomes, João; Kogan, Leonid 1974-; Yogo, Motohiro (Working paper series / National Bureau of Economic Research, 2007)
The demand for durable goods is more cyclical than that for nondurable goods and services. Consequently, the cash flow and stock returns of durable-good producers are exposed to higher systematic risk. Using the NIPA input-output tables, we construct portfolios of durable-good, nondurable-good, and service producers. In the cross-section, a strategy that is long on durables and short on services earns a sizable risk premium. In the time series, a strategy that is long on durables and short on the market portfolio earns a countercyclical risk premium. We develop an equilibrium asset-pricing model that explains these empirical findings.